Penentuan Jalur Optimal Menuju Stasiun Kereta Api Tawang Kota Semarang Menggunakan Analisis Jaringan - Nina Ratnaningrum; Bambang Darmo Yuwono; Moehammad Awaluddin (Departement Teknik Geodesi Universitas Diponegoro, 2014)
As the development of human life, roads as a means of transportation facing increasingly complex problems, which affect the use of the road network is mainly related to the travel time required to reach a location. Tawang railway station in Semarang City is one of the common facilities are often used by people as a long-distance mass transportation infrastructure During the development, people needs to reach Tawang railway station fast and optimal, views of time to reach the location at an interval of morning, afternoon, and evening.This research aimed to obtain information about the approximate travel time of traffic that will be very useful for the users of the road so that the road users can pick and choose the best travel interval at a predetermined route before traveling. Geographic Information Systems can be used as an alternative to analyze the road network and the travel time which determines the most optimal track towards the Tawang railway station, as well as analyzing the time the plan is prepared to road users could get the location on time. The calculation of travel time based on Travel Time Reliability that will give result Planning Time.The results obtained for an optimal route in the Mangkang Bus Station – Tawang Railway Station Route is via Jl. Imam Bonjol in the evening which has a length of 17.099 km road with Travel Time is 26.34 minutes, 48.79 minutes for Planning Time, and Validation Time is 30.81 minutes; the Terboyo Bus Station – Tawang Railway Station Route is via Jl. Letjend Suprapto at afternoon which has a length of 5.707 km road with Travel Time is 9.04 minutes, Planning Time is 16.79 minutes and 15.51 minutes for the Validation Time; the Penggaron Bus Station – Tawang Railway Station Route via Jl. Soekarno Hatta in the evening of a long road that has 10,694 km with Travel Time is 19.96 minutes, 35.82 minutes for Planning Time, and Validation Time is 20.49 minutes; and the Banyumanik Bus Station – Tawang Railway Station Route via Jl. MT. Haryono in the afternoon which has a length of 13.851 km road with Travel Time is 23.28 minutes, Planning Time is 48.79 minutes and 31.18 minutes for the Validation Time.Keywords : Geographic Information System, ArcGIS, Network Analysis, optimal track.